2002
DOI: 10.1256/0035900021643692
|View full text |Cite
|
Sign up to set email alerts
|

The 7.7‐year North Atlantic Oscillation

Abstract: SUMMARYWe present a statistical method, the extended canonical correlation analysis, to extract intermittent propagative coupled oscillations. We have applied this technique to a 136-year-long North Atlantic sea-level-pressure and sea-surface-temperature dataset. Nine ocean-atmosphere coupled oscillations with periods between 2.3 and 18 years were found. The 7.7 y period oscillation is presented in some detail and its links with the North Atlantic Oscillation are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 44 publications
8
40
0
Order By: Relevance
“…To this QD mode, the main contribution of the Atlantic Ocean comes from the regions sited to the south of Greenland, over the North Sea, and in the midlatitudes around 40°N (three upper latitudinal lobes of the SST3). Similarly to the results of Moron et al (1998) and da Costa and Colin de Verdiere (2002), this mode involves a phase opposition between the North Atlantic's subtropical and subpolar gyres, with a westerly intensification coinciding with a positive lobe off Cape Hatteras and negative lob off Newfoundland. In addition, we find that warm SST to the south of Greenland and cool SST to the south of Newfoundland and in the North Sea are related, with a delay of around 36 months, with warm LST in north-western Europe (or a few months earlier with opposite sign).…”
Section: Discussion and Concluding Remarkssupporting
confidence: 56%
See 1 more Smart Citation
“…To this QD mode, the main contribution of the Atlantic Ocean comes from the regions sited to the south of Greenland, over the North Sea, and in the midlatitudes around 40°N (three upper latitudinal lobes of the SST3). Similarly to the results of Moron et al (1998) and da Costa and Colin de Verdiere (2002), this mode involves a phase opposition between the North Atlantic's subtropical and subpolar gyres, with a westerly intensification coinciding with a positive lobe off Cape Hatteras and negative lob off Newfoundland. In addition, we find that warm SST to the south of Greenland and cool SST to the south of Newfoundland and in the North Sea are related, with a delay of around 36 months, with warm LST in north-western Europe (or a few months earlier with opposite sign).…”
Section: Discussion and Concluding Remarkssupporting
confidence: 56%
“…Below 20°N, weak SST anomalies of the same sign as the one off Newfoundland extend over most of the basin, except in the south-western part of the ocean. How this atmospheric-oceanic structure emerges is a currently debated question (da Costa and Colin de Verdiere, 2002;Novotná, 2004, 2008).…”
Section: Quasi-decadal Oscillation Of Lst1mentioning
confidence: 99%
“…Our finding of two dominant, 8-y and 12-y signals in the lake-level and precipitation time series is consistent with previous observational studies based on the analysis of instrumental record [26,27]. Near-decadal spectral peaks were also found to be ubiquitous in tree-ring-based proxy reconstructions of the Great Lakes water levels [32][33][34], as well as in such reconstructions of the NAO index known to be correlated with temperature and precipitation conditions over the Eastern and Central U.S. [35][36][37].…”
Section: Discussionsupporting
confidence: 93%
“…The North Atlantic SST's north-south dipole pattern is similar in structure to spatial patterns identified by Moron et al [26] (Figure 10) and Da Costa and De Verdiere [27] (Figure 2), who analyzed SSTs and SLP fields and found a 7.7-y oscillation possibly rooted in coupled dynamics; the time scale and pattern of this oscillation (not shown) is remarkably similar to the ones associated with the ~8-y oscillation in the Michigan-Huron water levels, thus further substantiating our findings that the 8-y wintertime lake-level cycle is driven by processes in the North Atlantic region as opposed to those associated with the PNA in the North Pacific. We thus conclude that the 8-y cycle is initiated by temperature changes in the North Atlantic which modify long-wave synoptic patterns thus altering moisture transport and precipitation totals in the Great Lakes' region, thereby producing quasi-periodic lake-level changes during the winter months.…”
Section: The Pacific/north American Indexsupporting
confidence: 80%
“…[15] A 7 -8-year peak exists in instrumental records of North Atlantic sea surface temperatures [Moron et al, 1998] and sea level pressure [Da Costa and Colin de Verdière, 2002], as well as in the North Atlantic Oscillation index [Wunsch, 1999]. Felis et al [2004] have shown 5 -6-year variability to persist in isotopic coral records from the northernmost Red Sea (Gulf of Aqaba) during the last interglacial, 120 kyr ago.…”
Section: Resultsmentioning
confidence: 99%